Pengaruh Inovasi, Dan Kreativitas Terhadap Keunggulan Bersaing Dalam Mencapai Keberhasilan Usaha Pada UMKM Di Kabupaten Buleleng - Sri Kasih, Ni Luh; Ayuni, Ni Made Sri; Ambara Wijaya, I Made (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
This study aims to find out how the influence of Innovation and Creativity through Competitive Advantage in achieving Business Success in Micro, Small and Medium Enterprises (MSMEs) in Buleleng Regency. This study uses a quantitative approach, with the data collection technique used is a questionnaire distributed by Google form media and directly with a measuring instrument in the form of a Likert scale, where the respondents were selected as owners of small and medium micro enterprises with a total of 99 business owners as respondents. The data analysis technique used in this study is a structural equation model (SEM) based on Partial Least Square (PLS) using the SmartPLS application. The results showed that Innovation, Creativity and Competitive Advantage had a positive and significant effect on Business Success, Innovation and Creativity had a positive and significant effect on Competitive Advantage, and Innovation and Creativity had a positive and significant effect on Business Success through Competitive Advantage